COMBINING SIMULATION WITH GENETIC ALGORITHM FOR SOLVING STOCHASTIC MULTI-PRODUCT INVENTORY OPTIMIZATION PROBLEM - Jackson, I. (Journal of Economic Research & Business Administration, 2019)
All companies are challenged to match supply and demand, and the way the company tackles this challenge has a tremendous impact on its profitability. Due to the fact that markets are rapidly evolving and becoming more complex, flexible, and information-intensive, notorious binging-andpurging approach is inappropriate. Scuh an approach, in which product is, firstly, overpurchased or overproduced in order to prepare for expected demand spikes and then discarded by sharp decline in price. Thus, in order to tailor inventory control to urgent industrial needs, the discrete-event simulation model is proposed. The model is stochastic and operates with multiple products under constrained total inventory capacity. Besides that, the model under consideration is distinguished by uncertain replenishment lags and lost-sales. The paper contains both mathematical description and algorithmic implementation. Besides that, an optimization framework based on genetic algorithm is proposed for deriving an optimal control policy. The proposed approach contributes to the field of industrial engineering by providing a simple and flexible way to compute nearly-optimal inventory control parameters.